A Study of Students’ Errors on Paragraph Writing - Krismonica, Dhenok; Harmanto, Bambang; Mustikawati, Diyah Atiek; Maghfiroh, Ana (LPPM Universitas Pancasakti Tegal, 2021)
Writing is one of the most important skills for foreign language students to master. Writing skill is essential since it is needed frequently in business and higher education. However, writing is one of the skills that is considered difficult by most students where they often make errors and mistakes. In the field of language learning, error analysis plays an important role. By knowing at least common mistakes, the students can learn and they will not make the same mistakes again in the future. This study concerns an analysis of students’ errors in paragraph writing. This study employed an observation research method to analyze the data from students’ tasks in paragraph writing. The data were collected, identified, and analyzed. The findings indicated that the most errors made by the students were in spelling and tenses. In addition, students’ errors were also found in verb arrangement.